Crescimento epitaxial e caracterização de filmes finos: óxidos condutores e ferroelétricos preparados por deposição de solução química - Capeli, Regina Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In this paper the citrates polymerized solutions with high chemical homogeneity of compounds of Perovskite structure composite systems Pb0,76Ca0,24TiO3(PCT24) e LaNiO3(LNO) were applied to prepare thin films textured/epitaxial. It was made the growth of PCT24 on LNO thin films deposited on single crystal substrates such as on LaAlO3 (100), LaAlO3 (001) and LaAlO3 (111) for verification of texturing and its preferred orientation. The dependence of the dielectric/ferroelectric and electronic transport properties with respect to texturing properties were evaluated for the formation of electronic devices for thin films PCT24 and LNO, respectively. It was also performed a comparative study of electrical properties of thin films with LNO base electrode and platinum. The effects of the arrangement and orientation of the ferroelectric domains as well as texturing, the electrical properties of ferroelectric films were evaluated and correlated with the crystallographic characteristics, microstructure and stoichiometric (chemical composition) of materials. Therefore, the possibility of obtaining ferroelectric this material opens a new front of research and perspectives with respect to the same job in different types of electronic devices.

Neste trabalho as soluções de citratos polimerizados com alto grau de homogeneidade química de compostos de estrutura perovisquita dos sistemas Pb0,76Ca0,24TiO3(PCT24) e LaNiO3(LNO) foram aplicadas para preparar filmes finos texturizados/epitaxiais. Foi feito o crescimento de filmes finos PCT24 sobre LNO depositados sobre substratos monocristalinos tais como LaAlO3(100), LaAlO3(001) e LaAlO3(111) para verificação da texturização e sua orientação preferencial. A dependência das propriedades dielétricas/ferroelétricas e das propriedades de transporte eletrônico com relação a texturização foram avaliadas para a formação dos dispositivos eletrônicos para os filmes finos PCT24 e LNO, respectivamente. Também foi realizado o estudo comparativo das propriedades elétricas dos filmes finos com eletrodo de base de LNO e de platina. Os efeitos da disposição e orientação dos domínios ferroelétricos bem como da texturização, nas propriedades elétricas de filmes ferroelétricos foram avaliados e correlacionados com as características cristalográficas, microestruturais e estequiométricas (composição química) dos materiais. Portanto, a possibilidade de obtenção de cerâmicas ferroelétricas deste material abre uma nova frente de pesquisas e perspectivas com relação ao emprego do mesmo em diversos tipos de dispositivos eletrônicos.
Epitaxial growth and characterization of thin films, conductive and ferroelectric oxides prepared by chemical solution deposition
Keywords: Filmes finos; Perovisquita; Ferroelétricos; Thin films; Perovskite; Ferroelectrics